2012
DOI: 10.2337/db11-1806
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial Platelet Activation Is Related to Postprandial Plasma Insulin Rather Than Glucose in Patients With Type 2 Diabetes

Abstract: Postprandial hyperglycemia is associated with platelet activation. We thus investigated if meal-induced platelet activation could be attenuated by meal insulin. A randomized, double-blind, cross-over study was performed to compare postprandial platelet activation after premeal injections of placebo or insulin aspart (0.1 and 0.2 units/kg) in 18 patients with type 2 diabetes mellitus (T2DM). Platelet activation was assessed by flow cytometry, without and with stimulation by the thromboxane analog U46619 or ADP.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 24 publications
3
23
0
1
Order By: Relevance
“…Previous studies have shown that hyperglycemia can increase platelet reactivity via an elevation of osmolality [28,29]. On the other hand, a recent study has shown that pre-meal treatment with insulin had an enhanced effect on post-meal platelet activation than postprandial hyperglycemia [30]. Our findings also showed post-load hyperglycemia did not increase platelet reactivity.…”
Section: Discussionsupporting
confidence: 64%
“…Previous studies have shown that hyperglycemia can increase platelet reactivity via an elevation of osmolality [28,29]. On the other hand, a recent study has shown that pre-meal treatment with insulin had an enhanced effect on post-meal platelet activation than postprandial hyperglycemia [30]. Our findings also showed post-load hyperglycemia did not increase platelet reactivity.…”
Section: Discussionsupporting
confidence: 64%
“…In contrast to the hypoglycaemic clamp where platelet activation was sustained or even further increased over the following 6 days, all platelet activation markers returned even numerically to baseline levels 1 week after the euglycaemic clamp. Hence, given the sample size of six people in the additional euglycaemic clamp experiment we can not entirely rule out an insulin infusion‐induced short‐term activation of platelets 1 day after the clamp, as has been shown previously in other settings . However, clearly the activation observed after the hypoglcaemia is more pronounced and sustainable for >1 week after the hypoglycaemic event.…”
Section: Discussionmentioning
confidence: 77%
“…Hence, given the sample size of six people in the additional euglycaemic clamp experiment we can not entirely rule out an insulin infusion-induced short-term activation of platelets 1 day after the clamp, as has been shown previously in other settings. 37 However, clearly the activation observed after the hypoglcaemia is more pronounced and sustainable for >1 week after the hypoglycaemic event. Based on the present study we cannot fully explain the mechanisms by which the platelet and coagulation activation after hypoglcaemia occurs, but considering the lifespan of platelets being 7 to 10 days, the observed sustained activation even 1 week after hypoglcaemia seems to be triggered by a subsequent mechanism following the blood glucose drop (eg, stress hormone release), which lasts longer than the low glucose level itself.…”
Section: Markers Of Endothelial Function and Inflammationmentioning
confidence: 99%
“…67 In particular, abnormal platelet function is observed not only with DM, 68 but also in the prediabetic state. 69 Both hyperglycemia and hyperinsulinemia could cause enhanced platelet aggregation via promotion of abnormal platelet activation and oxidative stress. [68][69][70] Collectively, potential benefits of antiplatelet drug therapy are strongly expected for diabetic patients; 71 however, the JPAD trial demonstrated that aspirin had no benefit in the primary prevention of cardiovascular events in Japanese diabetic patients.…”
Section: Candidates For Diagnostic and Predictive Surrogatesmentioning
confidence: 99%